การบำบัดน้ำชะมูลฝอยด้วยระบบเอสบีอาร์ ที่มีการเติมถ่านกัมมันต์ชนิดผง - จตุพร วงษ์จาด (จุฬาลงกรณ์มหาวิทยาลัย, 1999)
To investigate COD and color removal from landfill leachate by using BPAC-SBR system. The comparison of efficiencies in COD and color removal was done with varying powder activated carbon (PAC) concentration, sludge retention time (SRT), organic loading and application of co-metabolism to BPAC-SBR. In the experiment with a diluted landfill leachate, having COD 1,000 mg./l. (COD loading 0.571 kg/m3-d) and color 170.7 Su., the system with PAC (PL-75) concentration 20,000 mg/l, SRT 20 days had efficiencies in COD and color removal 75.6 and 75.4 %, respectively. Effluent COD and color were 246 mg/l and 42.1 Su.. Varying SRT to 30 days, efficiencies of COD and color removal decreased to 67.9 and 59.1%m repectively. The reason might be due to the longer SRT, the less amount of PAC addition to system. The main treatment mechanism was mainly due to the combination of adsorption by PAC and biochemical reaction. The variation of anaerobic-aerobic duration did not significant affect the COD and color reduction efficiencies. Increasing COD to 1.143 and 2.286 kg/m3-d, efficiencies of COD removal were 62.6 and 49.0% and efficiencies of color removal were 51.2 and 34.9%, respectively. The decreases in efficiencies may be caused by more amount of toxic organic and inorganic matters in the influent. This could be obstacle of bacteria mechanism and organic adsorption capacity by PAC. COD and color removal efficiencies were higher when co-metabolism concept was applies to BPAC-SBR by adding sugar to the landfill leachate. This influent had total COD of 2,000 mg/l, at the COD from sucrose : landfill leachate COD ratio of 1:1, and 188.3 Su. of color. This BPAC-SBR system could remove COD and color at 89.1 and 86.3%, respectively, the effluent concentrations in terms of COD and color were lower than those obtained in the case of normal BPAC-SBR.